2008
DOI: 10.1021/jp8022937
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Photoionization Cross-Section of the Methyl Radical

Abstract: The absolute photoionization cross-section of the methyl radical has been measured using two completely independent methods. The CH3 photoionization cross-section was determined relative to that of acetone and methyl vinyl ketone at photon energies of 10.2 and 11.0 eV by using a pulsed laser-photolysis/time-resolved synchrotron photoionization mass spectrometry method. The time-resolved depletion of the acetone or methyl vinyl ketone precursor and the production of methyl radicals following 193 nm photolysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
86
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 65 publications
18
86
0
Order By: Relevance
“…In Kiefer et al's work [5], the rate constants of R1 were measured in experiments and calculated by RRKM theory at various pressures (33,67,133,200 and 266 mbar) in the temperature range of 1300-2000 K. They suggested that the uncertainty of rate constants is within ±30% throughout the range of pressure and temperature. In this work, their calculated rate constant at 33 mbar is used and divided by a factor of 1.5 in the simulation to get a better agreement with the experimental measurement.…”
Section: Reactions Of Cyclohexanementioning
confidence: 99%
“…In Kiefer et al's work [5], the rate constants of R1 were measured in experiments and calculated by RRKM theory at various pressures (33,67,133,200 and 266 mbar) in the temperature range of 1300-2000 K. They suggested that the uncertainty of rate constants is within ±30% throughout the range of pressure and temperature. In this work, their calculated rate constant at 33 mbar is used and divided by a factor of 1.5 in the simulation to get a better agreement with the experimental measurement.…”
Section: Reactions Of Cyclohexanementioning
confidence: 99%
“…For these species, the quantitative profiles typically agree to within a factor of 2-4 between the EI and PI measurements, but discrepancies up to an order of magnitude are observed. For example, the photoionization cross section of the methyl radical had not been measured until recently [38] and no experimental value is available for the electron ionization process. The calibration factor in the electron ionization measurements was based on the convolution of the value calculated with the Binary Encounter Bethe (BEB) theory [39] with the experimentally determined electron-energy distribution function.…”
Section: Comparison Of Ei and Pi Mole Fraction Profiles -Implicationsmentioning
confidence: 99%
“…The ionization crosssections of CH3 and HCO are similar in magnitude near 118 nm and relatively small (~5×10 -18 cm 2 ). 42,53,54 However, ionization is universal. That is, the ionization efficiency is independent of the rovibrational state of the products, which readily compensates for the apparent limitation on the detection sensitivity.…”
Section: Resultsmentioning
confidence: 99%